Salt fog testing of polymer housed surge arresters. - Cherney, E.A (IEEE Transactions on power delivery)
This paper deals with the evaluation of the insulation design of polymer housed surge arresters for distribution lines. Five commercial designs were tested in a salt fog chamber for 9 cycles using a cycle consisting of 120 hours of salt fog that was followed by a 48 hour rest period for a total of 1280 hours of salt fog. In these tests, the specification for the 1000-hour salt fog test in IEC 1109 for composite insulators was used as a guide. The results demonstrate that a comprehensive evaluation of the external and internal insulation design of polymer housed surge arresters can be obtained by performing a salt fog test, and as such, the test can be considered as a useful design test. Suggestions for improvements in the insulation design of all polymer housed surge arresters evaluated are given in the paper